ANALISIS PERILAKU KONSUMEN TERHADAP KEGIATAN TRANSAKSI ONLINE MENGGUNAKAN PENDEKATAN RED OCEAN STRATEGY & BLUE OCEAN STRATEGY - Sonata, Derry Aryandi; Hapsari, Yaning Tri (Journal of Industrial Engineering and Technology, 2025)
This research aims to analyze consumer behavior towards online transaction activities using the Red Ocean Strategy and Blue Ocean Strategy approaches on the digital banking application "SeaBank." The study was conducted by sampling students from UPY. The research method used is quantitative with descriptive analysis. The results show that approximately 23% of UPY students have used SeaBank as their digital banking tool. The majority of SeaBank users (52%) are new users with less than one year of experience, while other application users (47%) tend to be long-term users. The frequency of application use shows that most students use e-wallets 1-3 times a week (49%) and 4-7 times a week (29%). User satisfaction levels for SeaBank in terms of security are as follows: very satisfied 48%, satisfied 35%, and neutral 17%. For convenience, very satisfied 39%, satisfied 44%, and neutral 17%. For ease of use, very satisfied 56%, satisfied 22%, and neutral 22%. Based on this research, it is recommended that SeaBank increase promotions through social media and referral programs, optimize transaction speed and security, and consider integrating additional features to add service value and keep up with the latest trends in digital finance.